Perbedaan Pendidikan Kesehatan Menggunakan Metode Audiovisual dan Booklet terhadap Peningkatan Pengetahuan Remaja Tentang Perilaku Seks Bebas [Comparing The Efficacy of Audiovisual and Booklet Methods in Enhancing Adolescent Understanding of Healthy Sexual Behaviour] - Mujiyanti, Sri; Wulandari, Anisa; Rachmaniah, Dini (Universitas Pelita Harapan, 2023)
Engaging in casual sex encompasses all behaviors driven by sexual desire, whether with individuals of the opposite gender or the same gender. The objective of this research is to examine the effectiveness of employing audiovisual media and booklet media in enhancing adolescents' understanding of casual sexual behaviors. This study employs a Quasi-Experiment with a one-group pre-test-post-test design methodology. The research population consists of 847 respondents, with a sample size of 32 respondents chosen through the Simple Random Sampling technique. Research findings reveal a disparity in knowledge acquisition between audiovisual media, with an average score of 14.69, and booklet media, with an average score of 13.94, demonstrating a significant level (p-value = 0.011). The research concludes that a meaningful distinction exists between the effectiveness of educating adolescents about casual sexual behaviors using audiovisual media versus booklet media. Based on these research outcomes, it is hoped that educational institutions will optimize the provision of sexual health education for adolescents, addressing the topic of casual sexual behaviors through both audiovisual and booklet media to prevent adolescents from engaging in sexually risky behaviors.BAHASA INDONESIA Perilaku seks bebas merujuk pada segala bentuk tindakan yang dipicu oleh dorongan seksual, baik itu dengan pasangan lawan jenis maupun sesama jenis. Tujuan dari studi ini adalah untuk menguji efektivitas penggunaan media audiovisual dan media booklet dalam meningkatkan pengetahuan remaja tentang perilaku seks bebas. Penelitian ini menggunakan metode Quasi Eksperimen dengan Desain One Group Pretest-Posttest. Populasi penelitian terdiri dari 847 responden, sampel terdiri dari 32 responden yang dipilih menggunakan Teknik Simple Random Sampling. Hasil penelitian menunjukkan bahwa terdapat perbedaan dalam pengetahuan antara kelompok yang menggunakan media audiovisual (rata-rata 14.69) dan kelompok yang menggunakan media booklet (rata-rata 13.94), dengan nilai p (p value) sebesar 0,011. Kesimpulan dari penelitian ini adalah bahwa terdapat perbedaan efektif antara penggunaan media audiovisual dan media booklet dalam penyuluhan tentang perilaku seks bebas. Berdasarkan hasil temuan ini, disarankan agar pihak sekolah memaksimalkan penggunaan pendekatan pendidikan kesehatan menggunakan media audiovisual dan booklet untuk menghadapi potensi perilaku seks bebas di kalangan remaja.